2015
DOI: 10.1186/s13104-015-1420-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating melanoma cells in choroidal melanocytic lesions

Abstract: PurposeTo detect and quantify circulating tumour cells (CTCs) in peripheral blood of patients with uveal melanoma primary non-metastatic tumours, and to analyze the possible relationship between CTCs and clinical risk factors.MethodsProspective study with two clinical groups: 4 patients diagnosed with choroidal nevus and 8 patients with choroidal melanoma prior to treatment. A single sample of 7.5 mL of peripheral blood was taken and the CTCs were isolated using a CellSearch system that captures positive cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 14 publications
3
33
0
2
Order By: Relevance
“…However, no significant relationship was found between the positivity of CTC and the clinical-pathological parameters of the lesions (basal diameter of the tumor and height of the tumor). 83 Our results above were corroborated by another recent article, conducted by Bidard and collaborators. In this work, the CTC count and DNA levels of tumor cells were associated with the presence of miliary liver metastases and with the volume of metastases.…”
Section: Dovepresssupporting
confidence: 89%
See 1 more Smart Citation
“…However, no significant relationship was found between the positivity of CTC and the clinical-pathological parameters of the lesions (basal diameter of the tumor and height of the tumor). 83 Our results above were corroborated by another recent article, conducted by Bidard and collaborators. In this work, the CTC count and DNA levels of tumor cells were associated with the presence of miliary liver metastases and with the volume of metastases.…”
Section: Dovepresssupporting
confidence: 89%
“…82 The mean serum level of this group of patients was 89.56 ng/mL compared to 37.39 ng/mL for the nevus group without associated risk factors and 32.98 ng/mL for the control group. 83 This indicates that DJ-1 could be a potential marker of malignant transformation of choroid nevi. On the other hand, Chen et al have related DJ-1 to the presence of UM metastases.…”
Section: Proteins Identified From Um Cells Cultured In Vitromentioning
confidence: 96%
“…Indeed, the presence and number of CTCs isolated by the same technique showed no significant association with prognostic parameters or with metastatic progression and no therapy-related changes [336]. A recent study reported the isolation of CTCs by immunomagnetic sorting of CD146 (MUC18)-positive cells, which were further characterized for high molecular weight melanoma-associated antigen (MEL) expression in four of eight patients with primary, not metastatic UM whereas no CTCs were found in four choroidal nevus patient [337]. The small patient sample did not allow a correlation of CTC number and prognosis.…”
Section: Biomarkersmentioning
confidence: 99%
“…Daneben bieten sich aber auch die Form und Größe des Nukleus als weitere Unterscheidungsmerkmale an [30] mithilfe eines Antikörpers, der gegen das CD146 gerichtet ist. Für die Abgrenzung gegen Leukozyten und Endothelzellen erfolgten weitere Immunfluoreszenzfärbungen [44]. Diese Fallserie berichtet, dass mittels des CellSearch-Systems bei 50 % der Patienten mit UM, jedoch bei keinem Patienten mit choroidalem Nävus ZMZs nachweisbar waren.…”
Section: Nachweismethoden Zirkulierender Melanomzellen (Zmz) Bei Chorunclassified